Experimental study of effect of glass cover tilt angle of solar still in winter season of India's composite climate - Kumar Chauhan V.; Kumar Shukla S. (My University, 2025)
The present work consists of an experimental investigation to find the effect of the tilt angle of the condenser surface of solar still (SS) on distilled water productivity and efficiency in the winter season in the metrological condition of Varanasi (25.2623°N, 82.9894°E), India. In this experiment, three models were fabricated with different tilt angles having the same basin areas. The first two models were single basin single slope (SBSS) type SS having tilt angles of 25° and 30° in southward facing. The third model was a single basin double slope (SBDS) type SS having a tilt angle of 15° facing toward the east–west direction. Generally, the latitude angle is used as a tilt angle however the present study revealed that the tilt angle varies according to season (sun-earth positioning) and affects productivity. The findings show the temperature difference between basin water and condenser glass cover is limited which is the driving force of the desalination process. The results showed that model-1, 2, and 3 give maximum yield of 760, 925, 320 ml/m2 of distilled water with maximum thermal and exergy efficiency of 17.15 % and 0.6 %, 17.25 % and 1.1 %, and 7 % and 0.3 % respectively over seven hours span. This investigation also reveals the heat retaining capacity of SS and effect of polystyrene coverage on glass cover that helps to obtain maximum nocturnal yield of 435, 735, 320 ml/m2 from model-1, 2, and 3 respectively on different days that make total distilled output to 1195, 1660, 560 ml/m2 on a particular day. In design perspective, the proper selection of tilt angle facilitates the seamless gliding of condensate to collecting troughs that mitigate the loss of condensate that falls into the basin before reaching to trough. © 2022 Elsevier Ltd